Effects of the COVID-19 mitigation measures on alcohol consumption and binge drinking in college students: a longitudinal survey - Vasconcelos, Margarida (2021)
The data presented in this study are openly available in FigShare at: 10.6084/m9.figshare.14755278 (accessed on 22 August 2021).